Pengaruh Media Sosial Dan Kepuasan Pelanggan Dalam Meningkatkan Hasil Jual Pada UMKM Pembudidayaan Jamur Tiram - Riska Wulandari; Ova Novi Irama (Forum Kerjasama Pendidikan Tinggi, 2022)
This paper aims to identify and explain the influence of social media and customer satisfaction to increase sales results. Entrepreneurship is a creative endeavor based on innovation to produce something new and have added value as well as provide the benefits of creating jobs and the results are useful for many people. In this modern era, the internet has almost become everyone’s primary need, social media has become a medium to create a new phenomenon in the world of economy. The method used is explanatory quantitative research, that entrepreneurs are expected to think creatively and innovatively that the influence of social media and customer satisfaction has an effect on entrepreneurship.